2012
DOI: 10.1093/database/bas015
|View full text |Cite
|
Sign up to set email alerts
|

CPPsite: a curated database of cell penetrating peptides

Abstract: Delivering drug molecules into the cell is one of the major challenges in the process of drug development. In past, cell penetrating peptides have been successfully used for delivering a wide variety of therapeutic molecules into various types of cells for the treatment of multiple diseases. These peptides have unique ability to gain access to the interior of almost any type of cell. Due to the huge therapeutic applications of CPPs, we have built a comprehensive database ‘CPPsite’, of cell penetrating peptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
165
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(171 citation statements)
references
References 24 publications
1
165
0
5
Order By: Relevance
“…Cell-penetrating peptides (CPPs) are capable of mediating penetration of the plasma membrane, allowing delivery of macromolecular cargos to which they are attached to cell interiors. CPPs are typically 10-30 amino acids long and fall into one of three major categories: arginine-rich, amphipathic and lysine-rich, and hydrophobic (Gautam et al, 2012). CPP delivery of cargos to the interior compartments of cells is potentially transformative as a research tool, diagnostic aid and therapeutic mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-penetrating peptides (CPPs) are capable of mediating penetration of the plasma membrane, allowing delivery of macromolecular cargos to which they are attached to cell interiors. CPPs are typically 10-30 amino acids long and fall into one of three major categories: arginine-rich, amphipathic and lysine-rich, and hydrophobic (Gautam et al, 2012). CPP delivery of cargos to the interior compartments of cells is potentially transformative as a research tool, diagnostic aid and therapeutic mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…1C), can be assigned to two distinct CPP families [4,5,7]: pepM is highly hydrophobic and contains two Pro residues, which is typical of the hydrophobic/Pro CPP family, and pepR is highly cationic (+12) and fits the requirements of the Arg/Lys-rich CPP family [4,5,7]. MCPEP, a computational tool that estimates the probability of occurrence of secondary structure in peptides (both in aqueous environment and when inserted in lipid bilayers) by Monte Carlo simulation [22], predicts that both peptides acquire a random coil conformation in water.…”
Section: Resultsmentioning
confidence: 99%
“…The two CPPs have different biochemical properties and may be considered new members of two different CPP classes [4,5,7]: Arg-rich CPP (pepR) and hydrophobic Pro-rich CPP (pepM). Our study reinforces the idea that the former uses endocytic and the latter nonendocytic mechanisms, thus supporting the view that CPP internalization routes are class-dependent [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These peptides have a helical secondary structure with the hydrophobic and hydrophilic domains. They use the charged region for cell membrane interaction and the hydrophobic region for membrane perturbation and translocation [29,39]. Moreover, several studies have shown that the presence of tryptophan and backbone spacing can affect the uptake efficiency as well as its mechanism [40].…”
Section: Introductionmentioning
confidence: 99%